Clinical health care indicators monitoring as an indicatior of health services quality and safety - Ovčina, Amer (Array, 2019)
Continuous progress in the nursing profession has a significant impact on the quality in the process of clinical care, which brings about new challenges and tasks for nurses to invest in new knowledge and skills. The healthcare process requires a systematic team approach in the design of evidence-based tasks, good clinical practice and clinical guidelines, documented standardized phenomena and evaluated measurements and tests. Measurement instruments and statistical tests of treatment effectiveness are used to assess the quality of health care provided. For a successful measurement and analysis of the quality of clinical care, it is necessary to have standardized healthcare documentation that allows treatment and outcomes monitoring. Qualitative and safety indicators are used to assess the quality of clinical health care, which represent a means of measurement, screening or warning. Monitoring Quality and Safety Indicators in Health Care Services is used as a guide to monitoring, evaluating and improving the quality of health care, and supporting services and organizational functions. In the field of health care, we measure the total treatment, outcome of the healthcare process, patient satisfaction, unwanted events,quality of life, etc.